Assessing the influence of maternal vitamin D deficiency in early pregnancy and subsequent improvement on perinatal outcomes and long-term child development: a retrospective cohort study - Ji Yeon Lee; Sang Hee Jung; Eun Hee Ahn; Hyun Mee Ryu (PLoS ONE, 2025)
This study examined perinatal and long-term outcomes where maternal vitamin D deficiency was present in early pregnancy but normalized in mid-pregnancy and deficiency during both early and mid-pregnancy. In this retrospective study, we reviewed the clinical records of 5,169 singleton pregnant women who received a test of serum 25-hydroxy-vitamin D [25(OH)D] two times in the first and second trimester in our hospital from 2016 to 2022. The level of 25(OH)D was categorized into deficiency (<10ng/mL), insufficiency (10–20ng/mL), and sufficiency (≥20ng/mL). Women were grouped based on 25(OH)D status across both trimesters: consistently deficient (DD), initially deficient then sufficient in the second trimester (DS), and consistently sufficient (SS). We evaluated obstetric and neonatal outcomes, including long-term neurodevelopmental assessments. Measurements in the first trimester indicated that 21.7% (n = 1,120) of women were vitamin D deficient, 41.1% (n = 2,127) insufficient, and 37.2% (n = 1,922) sufficient. There were no significant differences in the incidence of gestational hypertension and diabetes among the DD, DS, and SS groups. The rates of preterm birth before 34 weeks (aOR = 2.42, 95%CI[1.24–4.71], p = 0.010), necrotizing enterocolitis (aOR = 22.26, 95%CI[4.16–119.34], p < 0.001), and developmental delay (aOR = 4.46, 95%CI[2.41–8.27], p < 0.001) were elevated in the DD group compared to the SS group. These risks didn’t diminish even when vitamin D deficiency in the second trimester was corrected (DS). In conclusion, associations between low first-trimester 25(OH)D levels and heightened risks of preterm birth and long-term developmental outcomes are observed. As subsequent normalization of 25(OH)D levels may not fully mitigate these risks, incorporating vitamin D screening and intervention before pregnancy as part of routine preconception care could be beneficial in optimizing maternal and offspring outcomes.